ĐÁNH GIÁ TÁC ĐỘNG CỦA VI SINH VẬT ĐẾN CHẤT LƯỢNG NHIÊN LIỆU DIESEL (L-0,05-62) TRONG ĐIỀU KIỆN NHIỆT ĐỚI - Ngô, Cao Cường (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EVALUATION OF THE IMPACT OF MICROORGANISM ON THE QUALITY OF DIESEL FUEL (L-0.05-62) IN TROPICAL CONDITIONSIt is known that bacteria, yeast and fungi are potentially petroleum degrading microorganisms. In our study, we have found two bacterial strains and one yeast strain from imported diesel fuel grade L-0.05-62. The results of accelerated test according to the GOST 9023 - 74 in laboratory show that the diesel fuel can be affected by the microorganisms during long-term preservation in tropical conditions. After testing for 3 months the microorganisms change a number of parameters such as kinematic viscosity, closed cup flash point, sulfur and the acidity exceeding the threshold.